Role of Information and Communication Technologies in Knowledge Economy of India : Potentials and Threats - Sudan, Falendra K. (Gyan Management Journal, 2007)
The information and communication technologies (ICTs) play a vital role in knowledge economy and unleashing a society’s full social and economic potential. Indian information technology (IT) market has grown from 1.73 billion in 1994-95 to 19.9 billion in 2003-04, which accounts for 3.82 percent of gross domestic product (GDP) in 2003–04. It provides job opportunities to about a million people. India’s IT industry is likely to grow at a compounded annual rate of 38 percent to reach 77 billion by 2008 contributing to 20% of India’s anticipated GDP growth and 30% of its foreign exchange earnings and it is also expected to employ more than 2 million people and indirectly create another 2 million jobs. India’s effective transformation to a knowledge economy calls for it to act in many different policy domains, deepening, complementing, or reorienting ongoing reforms to use knowledge efficiently and sustaining development in the long term to achieve inclus